Alternatively packed dry molten globule-like intermediate in the native state ensemble of a multidomain protein - Mishra, Prajna; Jha, Santosh Kumar (Journal of Physical Chemistry B, 2017)
It has been difficult to quantify the degree of side-chain conformational heterogeneity in the native (N) state ensemble of proteins and the relative energetic contributions of the side-chain packing and the hydrophobic effect in protein stability. Here, we show using multiple site specific spectroscopic probes and tools of thermodynamics that the N state ensemble of a multidomain protein contains an equilibrium intermediate (I) whose interdomain region resembles a dry molten globule. In the I state, a tryptophan residue in the interdomain region is alternatively packed, but its secondary structure and intradomain packing are N-like. The I state also has a larger interdomain distance, but the domain-domain interface is dry and molten. Our results indicate that hydrophobic desolvation and side-chain packing are decoupled during protein folding and that interdomain packing interactions have an important energetic contribution in protein stability. Dynamic interconversion between alternatively packed N-like states could be important for multiple allosteric and ligand binding functions of this protein.